Efficacy and safety of glimepiride/metformin sustained release once daily vs. glimepiride/metformin twice daily in patients with type 2 diabetes. Issue 3 (22nd January 2013) - Hwang, Y.‐C.; Kang, M.; Ahn, C. W.; Park, J. S.; Baik, S. H.; Chung, D. J.; Jang, H. C.; Kim, K.‐A.; Lee, I.‐K.; Min, K. W.; Nam, M.; Park, T. S.; et al.
Summary Aims: The study investigated the clinical equivalence in reducing haemoglobin A1c (A1C) between glimepiride/metformin sustained release (GM‐SR) 2/500 mg, a fixed‐dose combination, once daily and glimepiride/metformin (GM) 1/250 mg, a fixed‐dose combination, twice daily in patients with type 2 diabetes (T2D). Methods: A multicentre, randomised, double‐blind, double‐dummy study was conducted in 14 hospitals in Korea. Inclusion criteria were age 30–75 years, T2D diagnosis no longer than 10 years previously, A1C between 7% and 10%, and body mass index < 40 kg/m2. A total of 207 subjects were randomised into the GM‐SR group (n = 101) or the GM group (n = 106). Participants were assessed at baseline, 8 weeks and 16 weeks after treatment. Results: After 16 weeks treatment, no difference in baseline‐adjusted changes of A1C (primary efficacy variable) was observed between the two groups (−0.59% for GM‐SR group vs. −0.61% for GM group, 95% CI: −0.17 to 0.21; p = 0.84). In addition, there were no significant differences in secondary efficacy parameters between the two groups, including changes in A1C up to week 8, changes in fasting plasma glucose (FPG) and 2‐h‐postprandial plasma glucose up to week 8 and week 16, response rate, drug compliance and hypoglycaemic events. However, there was a difference in baseline‐adjusted changes of FPG between the two groups (−1.01 mmol/l for GM‐SR group vs. −1.52 mmol/l for GM group, p = 0.01 in the intention to treat set). Conclusions: GM‐SR 2/500 mg once daily was as effective as GM 1/250 mg twice daily in lowering A1C. In addition, no difference was noted in hypoglycaemic events between the two groups.